Effects of surgical menopause and estrogen replacement therapy on serum paraoxonase activity and plasma malondialdehyde concentration - Kumru, S; Aydin, S; Aras, A; Gursu, MF; Gulcu, F (Karger, 2005)
Background: We have investigated the effects of surgical menopause and estrogen replacement therapy (ERT) on serum paraoxonase 1 (PON1) activity and plasma malondialdehyde (MDA) levels in surgically postmenopausal women. Methods: Thirty-six healthy perimenopausal women who underwent total abdominal hysterectomy and bilateral salpingo-oopherectomy for uterine myoma were enrolled in this study. Blood samples were taken from the subjects 1 day before surgery, 1 day before starting ERT ( 30 days after the operation) and on the 30th day after the start of therapy. Results: After surgical menopause, there were significant increases in plasma MDA levels (p < 0.05) and a decrease in serum PON1 activity (p < 0.05). ERT significantly increased the PON1 activity (p < 0.05) and reduced MDA levels (p < 0.05). There was a positive correlation between serum high-density lipoprotein cholesterol and PON1 activity (r = 0.7, p < 0.001, n = 36) and a negative correlation between serum PON1 activity and plasma MDA levels ( r = -0.63, p < 0.006, n = 36). Conclusions: The present study suggests that postmenopausal women tend to have high levels of plasma MDA and reduced PON1 activity, and ERT reverses these effects. The effect of ERT on lipid peroxidation seems to be associated with serum PON1 activity. Copyright (C) 2005 S. Karger AG, Basel.
Keywords: menopause; estrogen replacement therapy; lipid peroxidation; paraoxonase 1